THU0593 Multicentric osteolysis with nodulosis and arthropathy (MONA): report of the first lebanese family. (12th June 2018) - Dagher, R.; Saliba, E.; Rizkallah, M.; Fadous Khalife, M.C.; Megarbane, A.
Abstract : Background: "Multicentric Osteolysis with Nodulosis and Arthropathy" (MONA) also known as Winchester-Torg syndrome is a rare chronic skeleton disorder caused by matrix metalloproteinase 2 ( MMP2 ) deficiency. It is characterised by facial dysmorphism, subcutaneous fibrocollagenous nodules, carpal and tarsal osteolysis and interphalangeal joint erosions. Short stature and Osteopenia are frequent and heart defects have been described. As children first present with joint pain, swelling and stiffness, MONA is often misdiagnosed as Juvenile Idiopathic Arthritis (JIA). Objectives: We report the first Lebanese family with 3 siblings presenting MONA, two of which were diagnosed at first as JIA. Methods: The proband is the eldest boy born of consanguineous parents. At birth, a ventricular septal defect (VSD) was noted. At the age of 5 bone erosions and nodules in his hands and feet, and cuneiform vertebrae of unknown cause appeared. He was diagnosed with JIA. His pain partially improved with methotrexate and TNF agonist treatment; steroid injections were performed in wrists and permitted a gain in range of motion. Secondarily, Osteopenia was detected. The middle boy was examined at the age of 7; he had wrist arthritis and metacarpal tenosynovitis. He was known to have psoriasis. He was treated first with steroid injections then with NSAID and methotrexate with a good response but his condition slowly progressed to deviated fingers. The youngest boy suffered from foot pain and Kohler disease was diagnosed at the age of 4. Soon after he developed global stiffness of the foot with erosions and nodules. He had failure to thrive and a VSD was detected. Results: This family history along with the progressive coarsening of face features in the 3 siblings raised the possibility of a genetic disorder. Exome sequencing for skeletal dysplasia in the eldest boy detected a mutation in the MMP2 gene (NM_001127891:exon2:c.8A>G:p.Y3C). The same mutation was found in the 2 other siblings. Conclusions: These cases are to add to the 44 individuals coming from 27 different families, with molecularly proven MONA reported in the medical literature. This diagnosis should be raised in front of patients having resistant articular erosions with hand and feet nodules, despite anti-rheumatic drugs. Till date, no specific therapy is available and management is only supportive. In this described family, steroid injections were efficient when children presented with swelling and stiffness of joints and seemed to slow progression to erosion. References: [1] Bhavani GS, Shah H, Shukla A, Gupta N, Gowrishankar K, Rao AP, et al. Clinical and mutation profile of multicentric osteolysis nodulosis and arthropathy. Am J Med Genet A2016Feb;170A(2):410–7. [2] Azzollini J, Rovina D, Gervasini C, Parenti I, Fratoni A, Cubellis MV, et al. Functional characterisation of a novel mutation affecting the catalytic domain of MMP2 in siblings with multicentric osteolysis, nodulosis and arthropathy. J Hum Genet2014Nov;59(11):631–7. [3] Castberg FC, Kjaergaard S, Mosig RA, Lobl M, Martignetti C, Martignetti JA, et al. Multicentric osteolysis with nodulosis and arthropathy (MONA) with cardiac malformation, mimicking polyarticular juvenile idiopathic arthritis: case report and literature review. Eur J Pediatr2013Dec;172(12):1657–63. Disclosure of Interest: None declared